Expected Utility and Catastrophic Risk - Masako Ikefuji; Roger Laeven; Jan Magnus; Chris Muris (Tinbergen Institute, 2014)
An expected utility based cost-benefit analysis is in general fragile to its distributional assumptions. We derive necessary and sufficient conditions on the utility function of the expected utility model to avoid this. The conditions ensure that expected (marginal) utility remains finite also under heavy-tailed distributional assumptions. Our results are context-free and are relevant to many fields encountering catastrophic risk analysis, such as, perhaps most noticeably, insurance and risk management.
Keywords: D61; D81; G10; G20; Q05; 330; Expected utility; Catastrophe; Cost-benefit analysis; Risk management; Power utility; Exponential utility; Heavy tails